APLIKASI KOMPOS KULIT BUAH KAKAO DAN PUPUK UREA, TSP DAN KCl TERHADAP PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt) - Sasmita, Risa; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sweet corn is one of the crops that has a fairly large role in provide the nutritional needs of the people. One of the effort that can be do to improve the growth and production of sweet corn is fertilization. The aim of this research are to determine the effect of interaction of cocoa peel’s compost and Urea, TSP and KCl fertilizer on growth and yield of sweet corn and get the best dose of treatment. This research was conducted experimentally by using Randomized Design Group (RDG) factorial with two factors namely cocoa peel’s compost treatment consist of 4 levels namely 0 ton/ha (K0); 2,5 tons/ha (K1); 5 tons/ha (K2); 7,5 tons/ha (K3) and Urea, TSP and KCl fertilizer treatment consist of 4 levels namely (50 kg Urea; 37,5 kg TSP; 25 kg KCl)/ha (P1); (100 kg Urea; 75 kg TSP; 50 kg KCl)/ha (P2); (150 kg Urea; 112,5 kg TSP; 75 kg KCl)/ha (P3); (200 kg Urea;150 kg TSP; 100 kg KCl)/ha (P4) with 3 replications. The parameters focus on plant height, the ratio of editorial root, cob length without cornhusk, the number of rows and cob weight without cornhusk/plot. The result of this research shows that the interaction of cocoa peel’s compost and Urea, TSP and KCl fertilizer there is no real effect to all the parameters. Giving cocoa peel’s compost 7.5 tons/ha and fertilizer (200 g Urea, 150 g TSP and 100 g KCl)/ha is the best dose of treatment. Key word: Sweet corn, cocoa peel’s compost, Urea, TSP, KCl fertilizer